2007
DOI: 10.1002/mds.21376
|View full text |Cite
|
Sign up to set email alerts
|

Depression symptoms in movement disorders: Comparing Parkinson's disease, dystonia, and essential tremor

Abstract: Depression is common in Parkinson's disease (PD) and affects 30 to 50% of all patients. In contrast to the wealth of research on depression in PD, little is known about the occurrence of depression in other movement disorders. The primary objective of the current study was to determine whether the high prevalence of depression symptoms seen in PD is also found in other movement disorders, by directly comparing rates of specific depression symptoms and depression severity across PD, dystonia, and essential trem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(58 citation statements)
references
References 43 publications
6
46
2
3
Order By: Relevance
“…In contrast, we identified robust correlations between PSQI, symptoms of depression, and RLS in both patient groups. Frequency of depressive symptoms in our patients with focal dystonia was lower than reported before (34-40%) [10,11,20], probably because most earlier studies used more detailed scales or interviews than BDI alone. Nevertheless, depression was clearly more frequent in dystonia than in controls.…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast, we identified robust correlations between PSQI, symptoms of depression, and RLS in both patient groups. Frequency of depressive symptoms in our patients with focal dystonia was lower than reported before (34-40%) [10,11,20], probably because most earlier studies used more detailed scales or interviews than BDI alone. Nevertheless, depression was clearly more frequent in dystonia than in controls.…”
Section: Discussioncontrasting
confidence: 82%
“…23 Several reports had documented that depressive symptoms were elevated in patients who also had ET and the severity of these symptoms was correlated with tremor severity. 5,24 Clinicians have been aware of the high frequency of depression in ET, but the etiology of depression associated with ET is still unclear and little is known about whether depression in ET and depression in primary affective disorders share common clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…4 Accumulating evidence has demonstrated that depressive symptoms are common in ET. [5][6][7][8][9] Depression has a major impact on functional ability as well as the quality of life of patients with ET. 8,9 Furthermore, as well as being a secondary response to disease manifestations, depressive symptoms may be a primary feature of the underlying disease.…”
Section: Introductionmentioning
confidence: 99%
“…Similar issue has been discussed by Miller et al and the authors have presented a meaningful discussion resourceful for healthcare professionals in PD [92]. Commonly prescribed antidepressants have been found effective for the PD patients and alongside the medication, exercise, yoga and meditation are advised for better outcome [93,94].…”
Section: Types Of Psychological Abnormalities Depressionmentioning
confidence: 87%